Water extract of cacumen platycladi promotes hair growth through the Akt/GSK3β/β-catenin signaling pathway - Fu, Hangjie; Li, Wenxia; Weng, Zhiwei; Huang, Zhiguang; Liu, Jinyuan; Mao, Qingqing; Ding, Bin (Frontiers in Pharmacology, 2023)
Cacumen Platycladi (CP) consists of the dried needles of Platycladus orientalis (L.) Franco. It was clinically demonstrated that it effectively regenerates hair, but the underlying mechanism remains unknown. Thus, we employed shaved mice to verify the hair growth-promoting capability of the water extract of Cacumen Platycladi (WECP). The morphological and histological analyses revealed that WECP application could significantly promote hair growth and hair follicles (HFs) construction, in comparison to that of control group. Additionally, the skin thickness and hair bulb diameter were significantly increased by the application of WECP in a dose-dependent manner. Besides, the high dose of WECP also showed an effect similar to that of finasteride. In an in vitro assay, WECP stimulated dermal papilla cells (DPCs) proliferation and migration. Moreover, the upregulation of cyclins (cyclin D1, cyclin-dependent kinase 2 (CDK2), and cyclin-dependent kinase 4 (CDK4)) and downregulation of P21 in WECP-treated cell assays have been evaluated. We identified the constituents of WECP using ultra-high-performance liquid chromatography-quadrupole time-of-flight mass spectrometry (UPLC-Q/TOF-MS) and endeavored to elucidate their relevant molecular mechanisms by network analysis. We found that the Akt (serine/threonine protein kinase) signaling pathway might be a crucial target of WECP. It has been demonstrated that WECP treatment activated the phosphorylation of Akt and glycogen synthase kinase-3-beta (GSK3β), promoted β-Catenin and Wnt10b accumulation, and upregulated the expression of lymphoid enhancer-binding factor 1 (LEF1), vascular endothelial growth factor (VEGF), and insulin-like growth factor 1 (IGF1). We also found that WECP significantly altered the expression levels of apoptosis-related genes in mouse dorsal skin. The enhancement capability of WECP on DPCs proliferation and migration could be abrogated by the Akt-specific inhibitor MK2206-2HC1. These results suggested that WECP might promote hair growth by modulating DPCs proliferation and migration through the regulation of the Akt/GSK3β/β-Catenin signaling pathway.